Pertumbuhan dan kinerja indeks pasar sektoral dalam periode Ramadhan - Belva Eswan Pratiwi (Riset Akuntansi dan Portofolio Investasi, 2023)
Religious holidays such as "Ramadhan" and "Idul Fitri" are one of the economic events that contribute significantly to economic growth in Indonesia. This study aims to analyze the growth and performance of the non-primary consumer goods sector, the primary consumer goods sector, and the transportation and logistics sector from 21 March 2023 to 28 April 2023. This study finds that the transportation and logistics sector is a sector that has a high rate of return with high risk. In addition, this study also finds that the transportation and logistics sector generated good growth and performance of returns on risk during the “Ramadhan” and “Idul Fitri” period.